2020
DOI: 10.1155/2020/3907920
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Formula Gegen‐Qinlian Decoction for Type 2 Diabetes Mellitus: A Meta‐Analysis of Randomized Controlled Trials

Abstract: Background. Herbal formula Gegen-Qinlian Decoction (GQD) has been widely used in China for the treatment of type 2 diabetes mellitus (T2DM), but its efficacy and safety are unclear. Method. The studies were identified from the PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure database, Wanfang database, and VIP database using the keywords “Gegenqinlian” or “Gegen-Qinlian” or “Gegen-Qin-Lian” or “Ge Gen Qin Lian.” Relevant studies were selected according to predefined inclusion and exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
8
0
4
Order By: Relevance
“…Several studies have found that GQD can effectively improve the balance of glucose and lipid metabolism in vitro and in vivo and reduce insulin resistance [ 7 ]. Lin et al found that GQD can effectively improve the symptoms of diabetes and has less side effects through meta-analysis [ 29 ], which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have found that GQD can effectively improve the balance of glucose and lipid metabolism in vitro and in vivo and reduce insulin resistance [ 7 ]. Lin et al found that GQD can effectively improve the symptoms of diabetes and has less side effects through meta-analysis [ 29 ], which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…GGQL was first recorded in a famous ancient medicine treatise Shanghan Lun, compiled by Zhong-Jing Zhang in the Han Dynasty of Chinese history (202 BC-220 AD). In previous researches, it has been found that GGQL exerts a range of pharmacological activities, including anti-inflammation, antidiabetic, antioxidant, and immunoregulative effects [11][12][13][14]. Our research team has confirmed that GGQL could decrease the fasting blood glucose (FBG) in mice with diabetes and improve the oral glucose tolerance and insulin tolerance in rats with T2DM [15].…”
Section: Introductionmentioning
confidence: 58%
“…Although GGRT has not been clinically used to treat atopic dermatitis, herbal medicines, such as P. lobata, S. baicalensis, C. japonica, and G. uralensis, and their active compounds, including puerarin, licoricidin, and magnoflorine, were previously considered as candidates for treating atopic dermatitis [56][57][58][59][60][61][62]. In addition, previous experimental and clinical studies on GGRT revealed that the herbal formula has a pharmacological effect on diabetes mellitus, dyslipidemia, ulcerative colitis, and acute lung injury [14][15][16][17][63][64][65]. The mechanisms underlying the effect of GGRT on these diseases were estimated and evaluated by several in silico multi-omics and network pharmacological studies [14][15][16][17]64,66,67].…”
Section: Discussionmentioning
confidence: 99%